LAZ Sidogiri and Social Transformation Towards Economic Empowerment of Banyuwangi Community Based on Islamic Values - Fathoni, Sufyan (Universitas Siliwangi, 2025)
AbstractIntroduction to The Problem: Empowerment of the community economy based on Islamic values is a strategic issue in social development in Indonesia, especially amidst increasing economic inequality and the challenges of globalization. The Sidogiri Zakat Institution (LAZ), affiliated with Islamic boarding schools, plays an important role in addressing this issue through a structured Islamic philanthropic approach.Purpose/Objective Study: This study aims to analyze the strategy of the Sidogiri Zakat Institution (LAZ) in implementing Islamic values in the community economic empowerment program and its impact on social transformation.Design/Methodology/Approach: Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation.Findings: The results of the study indicate that LAZ Sidogiri implements two forms of fund distribution, namely consumptive and productive, with the support of programs such as caring for education, health, the environment, the economy, and needs-based social programs. Although various programs have been implemented in a structured manner, their implementation still faces a number of challenges, including limited professional human resources, a weak monitoring system, and negative perceptions from the community. The positive impact of the LAZ Sidogiri economic empowerment program is seen in increasing community access to capital assistance and business training, although the scope is still limited. This study concludes that strengthening socialization strategies, improving the quality of human resources, and institutional transparency are essential in order to expand the impact of the program and ensure the sustainability of social transformation based on Islamic values.Paper Type: Research Article